2021
DOI: 10.1007/s00170-021-07188-y
|View full text |Cite
|
Sign up to set email alerts
|

Copper additive manufacturing using MIM feedstock: adjustment of printing, debinding, and sintering parameters for processing dense and defectless parts

Abstract: In the present study, an additive manufacturing process of copper using extrusion 3D printing, solvent and thermal debinding, and sintering was explored. Extrusion 3D printing of metal injection moulding (MIM) feedstock was used to fabricate green body samples. The printing process was performed with optimized parameters to achieve high green density and low surface roughness. To remove water-soluble polymer, the green body was immersed in water for solvent debinding. The interconnected voids formed during sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 45 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…Previously published studies have shown that fast printing speeds decrease the green part density. The maximum possible printing speed of 24 mm/s is thus in a similar range to previously published optimum printing speeds of 20 mm/s [ 16 , 17 , 38 ]. By applying 4 mm/s increments, the resulting printing speed interval ranges from 4 to 24 mm/s, and those printing speeds that satisfy Equation (6) are highlighted in gray in Table 3 .…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Previously published studies have shown that fast printing speeds decrease the green part density. The maximum possible printing speed of 24 mm/s is thus in a similar range to previously published optimum printing speeds of 20 mm/s [ 16 , 17 , 38 ]. By applying 4 mm/s increments, the resulting printing speed interval ranges from 4 to 24 mm/s, and those printing speeds that satisfy Equation (6) are highlighted in gray in Table 3 .…”
Section: Resultssupporting
confidence: 80%
“…To keep changes to debinding and sintering as low as possible, the use of highly filled filaments is thus not preferable for the intended complementary green part production [ 6 ]. Screw-based extrusion, on the other hand, is suitable for this purpose, as it allows conventional MIM feedstock to be processed [ 5 , 15 , 16 , 17 , 18 ]. Yet, machine costs are typically about ten times higher than FFF printers, since print heads are equipped with complex and expensive screw geometries [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The size of the granulated feedstock needs to be controlled (<5 mm) to obtain stability during printing and reduce printing defects generated by air entrapment [133]. As reported by Singh et al [85], the granule feedstock, sized from 3 to 5 mm, can provide relative sintered density up to 94% after sintering. Likewise, Lieberwirth et al [41] reported that a granule size of 3 mm could be readily printed, yielding good appearance.…”
Section: Screw-based Mex (Sb)mentioning
confidence: 99%
“…Most metal MEX binders are based on multiple components of polymer, similar to MIM binders. Considering the screw-and plunger-based metal MEX, the binder requirement is not as demanding as that for the filament-based type, as the granulated MIM feedstock, which has already been fully developed, can be successfully used [36,41,61,68,84,85,87]. However, the filament feedstock requires high flexibility so that it can be easily spooled, handled and printed.…”
Section: Feedstockmentioning
confidence: 99%
“…To the authors’ knowledge, the literature on both the geometric and mechanical properties, porosity, and microstructure of sintered metallic specimens developed with the FFF technique combined with debinding and sintering stages is scarce. In recent years, several preliminary results have been undertaken on the processability or the mechanical properties of PDS-built sintered parts of 316L (Thompson et al , 2019; Liu et al , 2020; Parenti et al , 2018; Kurose et al , 2020; Hassan et al , 2021), and 17-4 PH stainless-steel (Gonzalez-Gutierrez et al , 2019; Wu et al , 2002; Lieberwirth et al , 2018; Godec et al , 2020; Suwanpreecha et al , 2021; Abe et al , 2021); Ti-6Al-4V alloy (Zhang et al , 2020; Singh et al , 2020); and copper (Singh et al , 2021; Gonzalez-Gutierrez et al , 2021; Singh et al , 2021) using self-produced highly filled metal polymer composite filaments. Parenti et al (2018) analysis of the processability of PDS manufactured 316L parts examined the microstructure, shrinkage and density of sintered parts.…”
Section: Introductionmentioning
confidence: 99%